The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.4049/jimmunol.0902281
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Unique Population of Tissue-Memory CD4+ T Cells in the Airways after Influenza Infection That Is Dependent on the Integrin VLA-1

Abstract: During the immune response to influenza infection, activated T cells are distributed to both lymphoid and extralymphoid tissues, including the infected airways where direct recognition of viral Ag-bearing cells takes place. The collagen-binding α1β1 integrin VLA-1 is essential for the development of memory CD8+ T cells in the airways, and although expressed by some CD4+ T cells, its significance has not been demonstrated. We investigated the role of VLA-1 on virus-specific CD4+ T cells during and after primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 52 publications
3
67
1
Order By: Relevance
“…In the immune system, resting leukocytes seldom express VLA-1 (37), with the exception of the liver-resident NK cells described here. More recently published studies, however, found that viral infection induced T cells to express VLA-1, which was required for retention and survival of antigen-specific memory T cells in extralymphatic tissues (38,39). In addition, CD49a expression was upregulated in both memory NK cells and memory CD8 + T cells in the MCMV infection model (40), suggesting that CD49a may be a common marker for memory lymphocytes.…”
Section: Discussionmentioning
confidence: 96%
“…In the immune system, resting leukocytes seldom express VLA-1 (37), with the exception of the liver-resident NK cells described here. More recently published studies, however, found that viral infection induced T cells to express VLA-1, which was required for retention and survival of antigen-specific memory T cells in extralymphatic tissues (38,39). In addition, CD49a expression was upregulated in both memory NK cells and memory CD8 + T cells in the MCMV infection model (40), suggesting that CD49a may be a common marker for memory lymphocytes.…”
Section: Discussionmentioning
confidence: 96%
“…The transfer of 1°effectors to unprimed mice can protect against lethal challenge (8)(9)(10), and studies demonstrating memory CD4 + T-cell protection in mice deficient for CD8 + T and B cells suggest that an important helper-independent protective contribution of memory CD4 + T cells may be mediated directly by the 2°e ffectors (11)(12)(13). In addition, IAV-specific 1°effector (7,10) and memory (14,15) CD4 + T cells isolated from the lung and from secondary lymphoid organs (SLO) display distinct functional and phenotypic characteristics. Whether 2°effectors comprise a similarly heterogeneous population is unknown.…”
Section: Cytokines | Viral Infection | Immune Regulationmentioning
confidence: 99%
“…There was no difference in tetramer staining MFI between CD103 + and CD103 -CD8 + T cells (data not shown). In addition, many FLUspecific cells in the lung expressed VLA-1 (α 1 β 1 integrin) (Figure 2, B and C), which in mice has been shown to be responsible for retaining influenza-specific memory CD8 + T cells in the lung by binding to the type IV collagen-rich basement membrane (20)(21)(22). Although VLA-1 is expressed mainly by CD103 + CD8 + lung T cells (15) (Supplemental Figure 3), both CD103 + and CD103 -FLU-specific lung T cells expressed VLA-1.…”
Section: Human Lung Cd8 + T Cells Expressing αE Integrin Are Ielsmentioning
confidence: 99%